Estimating standard errors in finance panel data sets: Comparing approaches - Mitchell A. Petersen (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2004)
In both corporate finance and asset pricing empirical work, researchers are often confronted with panel data. In these data sets the residuals may be correlated across firms and across time, and OLS standard errors can be biased. Historically, the two literatures have used different solutions to this problem. Corporate finance has relied on Rogers standard errors, while asset pricing has used the Fama-MacBeth procedure to estimate standard errors. This paper will examine the different methods used in the literature and explain when the different methods yield the same (and correct) standard errors and when they diverge. The intent is to provide intuition as to why the different approaches sometimes give different answers and thus give researchers guidance for their use.
Keywords: 330